2013
DOI: 10.4018/ijbce.2013070102
|View full text |Cite
|
Sign up to set email alerts
|

Portable Subcutaneous Vein Imaging System

Abstract: In medical domain, the identification and detection of veins is necessary for certain clinical procedures such as venipuncture and intra-venous applications. Vein imaging is also essential for diagnosis of vascular diseases. The current existing modalities for Vein Imaging are highly expensive and bulky. Thus a portable, cost-efficient Vein imaging system is proposed in this paper to view and locate subcutaneous veins. The system comprises of an IR Camera which has been fabricated with NIR LED’s of 880nm wavel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The OpenCV library contains a huge number of algorithms that can be used for augmented reality, image processing, face recognition, objects identifying, etc. [34]. The main screen shown in Fig.…”
Section: Mobile App Developmentmentioning
confidence: 99%
“…The OpenCV library contains a huge number of algorithms that can be used for augmented reality, image processing, face recognition, objects identifying, etc. [34]. The main screen shown in Fig.…”
Section: Mobile App Developmentmentioning
confidence: 99%
“…Vein imaging is critical for phlebotomy, which is an important process for most medical clinical applications. A study showed that approximately 90% of hospitalized patients may need peripheral cannulation for the intravenous route of treatment, with more than a billion venous punctures performed annually for diagnostic tests [1]. In the case of patients with shock, hypotension, trauma, or burns, in infants, the elderly, and the obese, the health personnel may find it difficult to detect vessels using traditional methods.…”
Section: Introductionmentioning
confidence: 99%
“…The haemoglobin derivate was discovered based on the absorption co-efficient of blood in the visible and NIR region. Sravani et al, (2013) have proposed a portable subcutaneous vein imaging system. The system comprises of NIR LED's of 800nm wavelength embedded in the IR web camera.…”
Section: Introductionmentioning
confidence: 99%
“…The system comprises of NIR LED's of 800nm wavelength embedded in the IR web camera. It has been shown that the proposed system was able to locate the various veins and proved to be potential device for intravenous applications like venipuncture and other clinical applications (Sravani et al, 2013).…”
Section: Introductionmentioning
confidence: 99%